Red-legged cormorant uses plastic as nest material in an artificial breeding colony of Atacama Desert coast. (November 2020) - Garcia-Cegarra, Ana M.; Ramirez, Roberto; Orrego, Rodrigo
Abstract: Plastic debris affects the survival of numerous marine species such as seabirds. Several studies have report ingestion and entanglement of seabird species in plastic debris but just few describe plastic presence in nests. Here we report the first evidence of a novel artificial nesting colony of red-legged cormorant ( Phalacrocorax gaimardi ) using plastic as nesting material in two major seaport structures in Northern Chile. We sampled 18 abandoned nests and determined that overall nests contained plastic: industrial polypropylene bulk bags (35%), plastic bags (33%) and fishing gear (10%). Plastic types differ among seaports, ENAEX (National Company of Explosives) seaport located near the main city contained plastic bags as predominant material while GNL (Liquid Natural Gas Company) seaport located near the industrial area contained bulkbag fibers. Further research should analyze debris in beaches nearby the nesting colony in order to assess whether red-legged cormorants have any plastic preference or if they use the most available in the nature. Graphical abstract: Unlabelled Image Highlights: First evidence of Phalacrocorax gaimardi using plastic as nesting material in the South East Pacific. The nesting colony is located in the artificial structure of two major seaports in Mejillones Bay. Plastics are incorporated to the nests due to the vicinities of industries and city to the nesting colony. Here we provide baseline for future studies to assess the impact of plastics in nests of red-legged cormorants.